2018
DOI: 10.1364/oe.26.009920
|View full text |Cite
|
Sign up to set email alerts
|

Improving axial resolution for holographic tracking of colloids and bacteria over a wide depth of field by optimizing different factors

Abstract: Improving the axial resolution for multiparticle three-dimensional (3D) holographic tracking is crucial but challenging. Here we study the impacts of incident light power, uniformity of the illumination as well as image pixel size on the axial tracking resolution for digital holographic microscopy (DHM). We demonstrate that the resolution highly depends on the image pixel size and the uniformity of the illumination. A 3D localization algorithm based on local-intensity-maxima searching and a Gaussian fit to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Hydroxyl radicals and hydrogen bubbles have both been confirmed to influence bacteria activity. , Although the agar diffusion assay experiment confirmed that the effect of the pH (7.0–8.0) on bacterial growth activity is minimal, the influence of OH – on its motility cannot be ruled out. We failed to observe any microbubbles larger than 200 nm formed on the surfaces throughout the entire experiment under all the EP conditions because DHM has a resolution of 200 nm for 40× objective (NA = 0.6) . This suggests that the pressure of hydrogen gas generated by EP is less than the saturated vapor pressure in the solution so H 2 will be resolved once they are generated instead of forming bubbles.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydroxyl radicals and hydrogen bubbles have both been confirmed to influence bacteria activity. , Although the agar diffusion assay experiment confirmed that the effect of the pH (7.0–8.0) on bacterial growth activity is minimal, the influence of OH – on its motility cannot be ruled out. We failed to observe any microbubbles larger than 200 nm formed on the surfaces throughout the entire experiment under all the EP conditions because DHM has a resolution of 200 nm for 40× objective (NA = 0.6) . This suggests that the pressure of hydrogen gas generated by EP is less than the saturated vapor pressure in the solution so H 2 will be resolved once they are generated instead of forming bubbles.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We failed to observe any microbubbles larger than 200 nm formed on the surfaces throughout the entire experiment under all the EP conditions because DHM has a resolution of 200 nm for 40× objective (NA = 0.6). 26 This suggests that the pressure of hydrogen gas generated by EP is less than the saturated vapor pressure in the solution so H 2 will be resolved once they are generated instead of forming bubbles.…”
Section: Discussion Of the Mechanism Of Ep In Prevention And Control ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The DHM used in this study was based on an in-line configuration integrated with an inverted microscope (IX-83, Olympus) for the 3D dynamic tracking of planktonic ES, as described previously. The chamber containing the ES suspension was illuminated in a defocused way using a collimated light-emitting diode (LED, λ = 505 nm, Thorlabs, USA). After equilibrium for 10 min, the focal plane was located 10 μm beneath the LGG bacterial layer of different densities.…”
Section: Methodsmentioning
confidence: 99%
“…3,16 For applications that target the detection of large objects (e.g., bacteria or cells) instead of small objects (e.g., biomolecule, nanoparticles or subcellular structures), a large depth-of-field is usually required. 18,19 Additionally, for applications that require long-term imaging of living microorganisms, sample handling and immobilization often constitute a significant challenge. Several microfluidic approaches have been proposed to facilitate such analyses, e.g., single-cell arraying 20 and single bacteria immobilization.…”
mentioning
confidence: 99%